Ecosophy in Pakpak Dairi community folklore - Widayati, Dwi; Lubis, Rosliana; Harahap, Nurhayati; Maha, Rachmad Fadillah (Research Journal in Advanced Humanities, 2024)
This research highlights the ecosophy in the folklore of the Pakpak Dairi community (PDC). This qualitative descriptive research uses the critical ecolinguistics approach of Stibbe. The data collection was carried out by using note-taking techniques. The data were in the form of words, phrases and sentences related to the environment (ecolinguistics) in the folklore "Berru Leto". From the analysis, it was found that ecosophy is related to the teaching of life, especially in the relationship between humans and humans, humans and the environment, and humans and God. From this representation, the folklore "Berru Leto" contains a positive assessment which aims to provide understanding in order to maintain relationships between humans and humans, especially children and parents. Apart from that, it is very necessary to maintain human relationships with the environment and human relationships with God. It contains constructive things for the environment and life because it contains wisdom. This folklore reveals and appreciates the issues of life and well-being of all species, promotes human well-being, promotes environmental understanding, and promotes the redistribution of resources. This will certainly contribute to the regional potential related to the environment if the wisdom of this story is still applied by PDC.